Resiliensi dan Mekanisme Pertahanan Diri Afiliator Generasi Z Dalam Ekosistem Kerja Digital - Maulana, Erfan; Adhitya Fariyanto,; Rauly Sijabat, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The Work from Anywhere & Anytime (WFAA) framework frequently offers a deceptive sense of autonomy for Generation Z affiliate marketers, who essentially face complex psychological constraints. This study investigates how the lack of tangible spatial and temporal boundaries facilitates self-exploitation in response to dynamic digital algorithms. Utilizing the Control Theory framework through a qualitative case study, the research reveals that absolute professional autonomy paradoxically acts as a catalyst for prolonged productivity anxiety. The findings identify two primary individual defense pillars: behavioral engineering via physical digital disconnection and cognitive restructuring to recalibrate the perception of rest urgency. This study concludes that psychological well-being literacy maintains an urgency equivalent to digital proficiency in securing the long-term professional existence of affiliate marketers. Within this paradigm, digital platforms have evolved beyond mere income-generating instruments into hybrid ecosystems: a productivity arena that functions simultaneously as a medium for emotional catharsis for its actors.